Village Economic Development Strategy Based on Economic Independence through Local Initiatives in Jenneponto Regency - Rahman, Abdul (Borong Newinera Publisher, 2023)
It has highlighted on the extent that the local efforts can change the prospects of economic self-sufficiency as well as the needs of the communities in Jenneponto Regency. Analyzing initiatives such as the agricultural cooperatives, the community-based enterprises (BUMDes) and the skills development programs for the community, the study aims at establishing how the programs help to improve the incomes per capital within households, promote unity within the communities and most importantly, the contribution of the programs towards the regional economic development. Through the use of lives interviews and case studies, the study therefore demonstrates the impact of collective action, value addition, and training in enhancing sustainable development. The results indicate positive economic trends and increased social cohesion; however, the drawbacks include restricted credit availability and market unpredictability. The findings from this research are beneficial for policymakers and stakeholder to better understand concepts of economic sustainability and to develop guidelines on how to strengthen local communities.